INCLUSIVENESS IN THE DESIGN OF CHILDREN’S SANATORIUMS - Марчанчин, Анна; Дулька, Ольга; Шидловська, Олена; Іщенко, Тетяна (SWorldJournal, 2024)
The social significance of the problems of children with disabilities lies in the fact that this category of the population needs special attention, support and resources for full development, education and integration into society. Children with disabili